Social and emotional competences as predictors of student engagement in youth: A cross-cultural multilevel study - Santos, A. C.; Arriaga, P.; Daniel, J.; Cefai, C.; Melo, M. H. S.; Psyllou, A.; Shieh, J. -J.; Schutte, N.; Furtado, C.; David, C. H.; Azevedo, M. C.; Andreou, E.; et al. (Studies in Higher Education, 2023)
Student engagement research in university students has been scarce,despite its major positive role on performance, degree completion, and mental health. Social and emotional competencies, which are currently called twenty-first-century skills, exert some impact on student engagement in youth. Since engagement is cultural-sensitive, individual (social and emotional competencies) and cross-cultural (human developmental index and unemployment rate) characteristics were examined in association with student engagement in youth. This study included 2,092 participants from nine countries/regions, aged between 17 and 27 years (M = 21.52, SD = 2.27), mostly cisgender woman (n =1,035, 68.7%) and undergraduate (n = 1,401, 96.2%). Data were collected using a cross-sectional online survey that included the Student Engagement Scale, the Emotional Skills and Competence Questionnaire, and the prosocial behavior/resources subscale of the Strengths and Difficulties Questionnaire. Multilevel models showed that social and emotional competencies were relevant predictors of student engagement independently of the country-level variables. Moreover, student engagement varied with country/region human development and unemployment rate, with students from higher developed countries/regions and lowered unemployment reporting lower engagement. This study reinforces the need to implement evidence-based social and emotional learning programs in universities worldwide, as well as public policies that can influence engagement and protect youth.